(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Rabindranath Tagore‟s ideas and pedagogical philosophy are incomparable and unprecedented. Even in his most famous poems, Rabindranath emphasises the key issues: the independence of thinking and speech, active communication, blending nature and man, and the encouragement of the highest possible level of creative expression. Naturalism, idealism, humanism, and internationalism formed the basis of his educational philosophy. This paper discusses Rabindranath Tagore‟s educational philosophy and its practical implications.